Collapse of HSLA steel pipes under corrosion exposure and uniaxial inelastic cycling. (May 2018) - Talebi, M.; Zeinoddini, M.; Mo'tamedi, M.; Zandi, A.P.
Abstract: High strength low alloy (HSLA) steel pipes such as API-X80 and beyond, have found increasing applications in deep offshore hydrocarbon development projects. The current paper reports the results of inelastic uniaxial cyclic creep and incremental collapse experiments on API X80 steel pipes at different accelerated corrosion exposure. Effects of parameters such as the exposure duration, corrosion morphology and loading conditions on the monotonic response, cyclic response, local deformation mode, number of cycles to failure and modes of failure were examined. The corrosion morphology as well as the deformations in the pipe specimens were recorded and monitored using non-contact 3D optical measurement techniques. In relative terms, the corrosion effects were much more pronounced under cyclic loading than monotonic loading. The rate of the cyclic creep and the number of cycles to failure were radically affected by the corrosion exposure. The corrosion morphology had, comparatively, smaller effects. Uncorroded specimens showed axisymmetric ductile modes of failure. The failure mode in corroded specimens was non-axisymmetric and also included a brittle low-cycle fatigue failure mode. Highlights: Cyclic incremental collapse of corroded HSLA steel tubes was experimentally studied. The initial strain and corrosion expedited the incremental collapse and its rate. Local deformation modes were wrinkling in uncorroded but kinking in corroded tubes. Failure modes were ductile in uncorroded but brittle/ductile in corroded tubes.